Circuit-based basic motor activity games: An innovative solution to improve the movement skills of children with dyspraxia in the context of physical education - Satria, M. Haris; Ramadhan, Nurman; Aliriad, Hilmy; Da’i, Mohamad (Edu Sportivo: Indonesian Journal of Physical Education, 2023)
Dyspraxia in children is not a hindrance in training motor skills. The purpose of this study was to analyze the effect of gaming circuit-based interventions on their motor skills. This research method used one group experimental design with pretest-posttest design. The population of the study subjects were students with dyspraxia, with a sample consisting of seven purposively selected students. The instrument used was a series of four-pole games designed to measure students’ motor skills. The research procedure began by pretesting the students’ motor skills before the intervention. Then, a game circuit-based intervention was performed on all students over a period of time. After the intervention was completed, a posttest was performed to re-measure the students’ motor skills. Data from pretest and posttest were analyzed using SPSS statistical software version 23 to compare scores before and after the intervention. These findings provide positive support to the use of a game-based approach in improving the gross motor skills of children with dyspraxia in the context of physical education. The positive implication of this study is that the circuit game approach can enrich educational interventions for children with dyspraxia and provide better insight into the development of motor skills in this population through innovative approaches. It is recommended that further research focus on specific elements of circuit play that are most effective in improving gross motor skills in children with dyspraxia, with the potential to form better guidelines in physical education.